The 'right' side of the law: state of siege and the rise of fascism in interwar Romania - Cercel, Cosmin Sebastian (Brill Academic Publishers, 2013)
The aim of this article is to problematize one of the most audacious tenets of the new consensus, namely the revolutionary character of fascism, by linking together the experience of the state of siege and the emergence of the fascist movement in interwar Romania. It tries to do so by drawing on the philosophical underpinnings of the paradigm of the state of exception developed by Giorgio Agamben and Walter Benjamin’s critique of law and violence. In a first part my aim is to present the main arguments espoused in defending the view according to which fascist movements were professing an authentic revolutionary radical politics. Secondly, I will turn towards legal critique and to the work of Giorgio Agamben in order to build a topography of the relation between law and the force of state. In a third part I will focus on the uses and the historical meaning of the state of siege in post-First World War Romania. This article argues that the emergence of the fascist movement in Romania is an event strongly embedded in the political, legal and symbolic dynamics entailed by the state of exception rather than the expression of a revolutionary thrust.